Experiment and Numerical Simulation of Aerodynamic Performance of Compressor with Damaged Blades - H. Sun; Z. Wang; G. Luo (Journal of Applied Fluid Mechanics)
The present work attempted to lay a basis for evaluating the compressor aerodynamic performance in service environments. To achieve this goal, a low-speed compressor along with a transonic compressor rotor (NASA Rotor37) were studied. Different damaged blades were established, and three-dimensional viscous flow field simulations were accomplished. The influence of blade damage and the mechanism through which blade damage affects the compressor aerodynamic properties were analyzed. Further, the established numerical method was validated through low-speed compressor experiments. The results showed high resemblance of the simulations to the experimental findings, thus proving the effectiveness of our numerical simulation method. After the blade was damaged, the surge point of the compressor was advanced, the stable working flow range was reduced, and the aerodynamic performance was significantly reduced. The local airflow separation caused by the attack angle enlargement due to the deformation of blade after damage was the primary reason for the whole row of rotors to enter an unstable state. Unlike low-speed compressor, the rotor blade damage of transonic compressor caused the interference of shock wave with the boundary layer separation, and the burst low-speed region blocked the blade channel. This deteriorated the rotor flow state and caused greater flow loss, resulting in a more severe decline in the aerodynamic performance. The proposed numerical simulation approach for aerodynamic performance can effectively predict the steady-state aerodynamic performances of compressors with damaged blades.